A Massive Extradural Hematoma in Sickle Cell Disease and the Importance of Rapid Neuroimaging. (18th December 2019) - Iversen, Per Ole; Jacob, Mboka; Makame, Jamila; Abisay, Mclean; Yonazi, Mbonea; Schuh, Anna; Makani, Julie
Abstract : Sickle cell disease (SCD) is an inherited hemoglobinopathy leading to several serious organ complications and early death. It is mostly found in equatorial countries like Tanzania. Extradural hematoma (EDH) is a rare, but serious complication to SCD and may have debilitating consequences. Hitherto, there is no report of EDH in SCD where neuroimaging has been available before, during, and after such an event. Here, we describe a young female SCD patient who developed EDH that required surgical evacuation. She had made full recovery after three months. Neuroimaging performed two years prior to this event was unremarkable except for multiple small cerebral infarcts. On admission, neuroimaging revealed a subgaleal hematoma, possibly indicating disruption of the skull cortex due to increased hematopoiesis. Three months after evacuation of the hematoma, neuroimaging showed evidence of brain atrophy and the previously reported cerebral infarcts and multifocal bone infarction, but no vasculopathy. Possibly, disruption of the skull cortex with subsequent bleeding caused the EDH. As the differential diagnoses of neurological complications in SCD are many and some complications are reversible, neuroimaging should be performed without delay.